A Brief History Of Philology In Egypt: A Literary Study - Sayyed Zuhdi Abdil Ghany (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this research is to provide a brief overview of the history of philology and writing activities in Egypt, Egypt's position in the development of scholarship, as well as the claim that the first philological activities were undertaken by Islamic scholars. Egypt was chosen due to its significant role in the field of philology, especially during the 3rd century BC when the Greek civilization was present in Alexandria. This research is a qualitative research employing the method of literature review. Literature review involves the analytical examination of a collection of written sources, such as books, journals, and articles, relevant to the research topic. This research reveals that Egypt is a pioneer in the field of manuscript studies in the Middle East. To this day, Egypt continues to play a central role, as evidenced by the return of the headquarters of the Arab Manuscripts Institute to Cairo in 1991 and to the present day. The claims of several Arab researchers that Arab-Islamic scholars were the first to establish the foundations of philological theory hold strong rationale, considering that the theory and methods of tahqiq had already been developed thoroughly by hadith experts long before the literary revitalization projects in the West.